2020
DOI: 10.3390/su12208401
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Urban Air Pollution Emission Density on Air Pollutant Concentration Based on a Panel Model

Abstract: In terms of urban planning, the impact of urbanization and high density on the environment is a major issue. This study intended to analyze the effect of spatial density characteristics of urban air pollution sources on urban air pollution concentration using a panel model. As the total population density, the number of cars registered per capita, and the total emission facility density increased, together with a closer distance to a thermal power plant, the nitrogen dioxide(NO2) concentration increased. Net p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Regarding the other two regions (ET and TB), the deposition was considerably lower (5%-6%). These findings are in agreement with those of Vu et al who found that the majority of particles (number) were deposited in the AI region, with the deposition fraction in the AI region being equal to 0.35 when walking in an outdoor traffic area in Italy [8] . The corresponding values for TB and AI were 0.09 and 0.07, respectively.…”
Section: Diurnal and Seasonal Variation Of Deposited Number Dose Ratesupporting
confidence: 93%
See 4 more Smart Citations
“…Regarding the other two regions (ET and TB), the deposition was considerably lower (5%-6%). These findings are in agreement with those of Vu et al who found that the majority of particles (number) were deposited in the AI region, with the deposition fraction in the AI region being equal to 0.35 when walking in an outdoor traffic area in Italy [8] . The corresponding values for TB and AI were 0.09 and 0.07, respectively.…”
Section: Diurnal and Seasonal Variation Of Deposited Number Dose Ratesupporting
confidence: 93%
“…These peaks were influenced by domestic heating emissions; therefore, increased dose rates were obtained. The opposite characteristic was observed by Vu et al, where the diurnal variation of the number dose rate in Bologna (Italy) showed two peaks with the afternoon peak (16 × 10 9 particles/h) being lower than the morning peak (22 × 10 9 particles/h) [8] . According to Aalto et al, the maximum particle number concentrations (between 7 nm and a few micrometers) in five European cities (Augsburg, Barcelona, Helsinki, Rome, and Stockholm) were detected in the morning hours during weekdays, while the opposite characteristic was observed on Sunday, indicating that traffic emissions influence the diurnal behavior [32] .…”
Section: Diurnal and Seasonal Variation Of Deposited Number Dose Ratementioning
confidence: 72%
See 3 more Smart Citations